Characterization of TL and CW-OSL signals of natural brazilian topaz with different colours (Brazilian Journal of Radiation Sciences, 2021)
Topaz [Al2SiO4(OH,F)2] is usually found in nature and can presents different colours. The aim of this paper is to evaluate the thermoluminescence (TL) and the optically stimulated luminescence (OSL) response of five types of topaz collected from three different Brazilian states. The topaz samples studied have a yellow, blue and colourless coloration. The TL results showed that colourless samples from the state of Rio Grande do Norte present a TL glow curve with a main peak at ~260ºC. The others colourless topaz from Teofilo Otoni e Mato Grosso do Sul, besides the peak of ~260ºC, the present another peak at 160 ºC. The highest TL intensity was observed with the colourless topaz from RN. A linear TL dose curve response was also observed with these samples from the gamma radiation of 60Co in the range of 0.01 Gy to 3.5 Gy. The blue light stimulation (BSL) showed almost the same intensity response for the three colourless topaz samples. None topaz sample showed response to optical infrared stimulation (IRSL).
Keywords: Brazilian topaz; different colours; thermoluminescence (TL); optically stimulated luminescence (OSL).